2010
DOI: 10.2967/jnumed.108.059584
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluation of PET and PET/CT in Oncology: Evidence and Methodologic Approaches

Abstract: PET and PET/CT have changed the diagnostic algorithm in oncology. Health care systems worldwide have recently approved reimbursement for PET and PET/CT for staging of non-small cell lung cancer and differential diagnosis of solitary pulmonary nodules because PET and PET/CT have been found to be cost-effective for those uses. Additional indications that are covered by health care systems in the United States and several European countries include staging of gastrointestinal tract cancers, breast cancer, maligna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
41
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(43 citation statements)
references
References 46 publications
0
41
0
2
Order By: Relevance
“…Bu bulgunun daha geniş hasta serilerinde prospektif olarak değerlendirilmesi gerektiğini düşünmekteyiz. PET-BT incelenmesi birçok tümörde metastaz taramasında yaygın olarak kullanılmasına karşılık güncel verilere göre bazı avantajları ve bazı dezavantajlara sahiptir 12 . Yüksek riskli melanom hastalarında nodal hastalık saptanmasında pozitif prediktif değeri ve uzak metastaz saptanmasında negatif prediktif değeri yüksek bulunmuş, bazı çalışmalarda ise MR ile karşılaştırıldığında pulmoner ve hepatik metastazların saptanmasında MR inceleme tekniğinin PET-BT'den daha üstün olduğu savunulmuştur [12][13][14] .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Bu bulgunun daha geniş hasta serilerinde prospektif olarak değerlendirilmesi gerektiğini düşünmekteyiz. PET-BT incelenmesi birçok tümörde metastaz taramasında yaygın olarak kullanılmasına karşılık güncel verilere göre bazı avantajları ve bazı dezavantajlara sahiptir 12 . Yüksek riskli melanom hastalarında nodal hastalık saptanmasında pozitif prediktif değeri ve uzak metastaz saptanmasında negatif prediktif değeri yüksek bulunmuş, bazı çalışmalarda ise MR ile karşılaştırıldığında pulmoner ve hepatik metastazların saptanmasında MR inceleme tekniğinin PET-BT'den daha üstün olduğu savunulmuştur [12][13][14] .…”
Section: Discussionunclassified
“…PET-BT incelenmesi birçok tümörde metastaz taramasında yaygın olarak kullanılmasına karşılık güncel verilere göre bazı avantajları ve bazı dezavantajlara sahiptir 12 . Yüksek riskli melanom hastalarında nodal hastalık saptanmasında pozitif prediktif değeri ve uzak metastaz saptanmasında negatif prediktif değeri yüksek bulunmuş, bazı çalışmalarda ise MR ile karşılaştırıldığında pulmoner ve hepatik metastazların saptanmasında MR inceleme tekniğinin PET-BT'den daha üstün olduğu savunulmuştur [12][13][14] . Ameliyat öncesi dönemde, erken evre deriye sınırlı melanomlarda, PET-BT incelenmesi ile yalancı pozitiflikler saptanabileceğinden, hastalarda gereksiz endişelere neden olmamak için bu tekniğin uygulanması önerilmemektedir 11 .Yine dört görüntüleme yöntemini (PET-BT, ultrasonografi, MR ve BT) karşılaştıran bir başka çalışmada ise ultrasonografinin, lenf nodu metastazı saptamada en yüksek özgünlük ve özgüllüğe ve en yüksek prediktif değere sahip olduğu bunun yanında ise uzak metastazların saptanmasında PET-BT'nin en yüksek özgüllüğe sahip olduğu belirtilmiştir.…”
Section: Discussionunclassified
“…[6] PET/CT imaging of the breast offers physiological information complementary to that achieved from conventional imaging techniques and, therefore, can be used as better characterization of the disease. [7] Assessment of the response to therapy by PET/CT is based on reduction of the tumor FDG uptake, which represents reduced glucose metabolism in the cells which reflects cell death. Preliminary studies on small cohorts of patients have shown a correlation between early reduction of tumor FDG uptake and clinical response after completion of neo-adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic effectiveness of PET/CT for staging NSCLC and differential diagnosis of solitary pulmonary nodules has been recently approved by many health care systems worldwide. Additional indications for cancer imaging which are recognized in the USA and several European countries include staging and restaging of oesophageal, colorectal and breast cancer, malignant lymphoma, melanoma and head and neck cancer [2]. Regarding these indications, a diagnostic effectiveness and superiority to conventional cancer imaging modalities has been demonstrated.…”
mentioning
confidence: 99%
“…Given the paucity of available data, the work is important and clearly illustrates the need for future studies evaluating the cost-effectiveness of PET/CT, considering also emerging diagnostic modalities such as endobronchial ultrasound (EBUS) for mediastinal staging of NSCLC. Suitable designs for future clinical trials assessing cost-effectiveness or analysing cost-utility and cost-benefit of PET/CT for cancer imaging have been recently suggested [2].…”
mentioning
confidence: 99%